Ammonius on Universals and Abstraction: An interpretation and Translation of Ammonius’ In Porphyrii Isagogen 39, 8-42, 16 - Fortier, Simon (Laval théologique et philosophique)

(untitled) (Faculté de philosophie, Université Laval, 2012)
AbstractAmmonius’ is the earliest exegesis we possess of Porphyry’s Isagoge, as is his interpretation of lines 1.9-12, over which so much ink was subsequently spilt. Although the essence of this interpretation, the so-called doctrine of the three states of the universal, is now widely known, the section of commentary in which it appears has hitherto never been translated in its entirety. The following article therefore presents a complete translation of Ammonius’ commentary upon Isagoge 1.9-12, preceded by a brief introduction.